1964
DOI: 10.1172/jci104971
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Sequestration in Man. II. Immunological and Clinical Studies*

Abstract: The mechanisms of platelet destruction and their sites of sequestration in disease states are poorly understood. Although recent studies have emphasized the importance of platelet isoantibodies in certain clinical situations (1-3), little is known of the effects of antibodies on platelets in vivo. In conditions such as idiopathic thrombocytopenic purpura, there is debate as to whether immune mechanisms are involved, and sites of platelet sequestration are unknown.The availability of a method for labeling plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
1

Year Published

1966
1966
2017
2017

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 136 publications
(43 citation statements)
references
References 21 publications
3
39
0
1
Order By: Relevance
“…This finding is particularly surprising in view of the exquisite sensitivity manifested by platelets in vivo to a variety of antibodies (11,41,42). We have found that serum and plasma taken from two of the patients with PNH were as effective as normal plasma as a source of C' for platelet lysis, a finding suggesting that failure of PNH platelets to lyse in vivo is not due to deficiency of a plasma factor required for lysis.…”
Section: Resultsmentioning
confidence: 90%
“…This finding is particularly surprising in view of the exquisite sensitivity manifested by platelets in vivo to a variety of antibodies (11,41,42). We have found that serum and plasma taken from two of the patients with PNH were as effective as normal plasma as a source of C' for platelet lysis, a finding suggesting that failure of PNH platelets to lyse in vivo is not due to deficiency of a plasma factor required for lysis.…”
Section: Resultsmentioning
confidence: 90%
“…A significant deviation from these values after transfusion of platelets indicated that platelet-5Cr was concentrated (relative to erythrocytes) in a particular site. Previous studies have suggested that actual total radioactivity in normal-sized organs can be crudely estimated from external scanning with various standards for comparison (12,(16)(17)(18). Direct assay of 'Cr in three surgically removed normal-sized spleens (idiopathic thrombocytopenic 1 Nuclear-Chicago DS-301 scintillation detector with 3-inch diameter crystal and collimator 3 inches wide and 3 inches deep and 132B spectrometer-scaler with window at 100 kv.…”
Section: Methodsmentioning
confidence: 99%
“…J.) and polyvinyl chloride tubing into polypropylene tubes containing 1/10 vol of 3.8 g/100 ml of trisodium citrate dihydrate or 1/6 vol of the acid citrate anticoagulant of Aster and Jandl (18) or sodium heparin (final concentration 5 U/ml). Platelet-rich plasma (PRP) was prepared by centrifugation at 150-200 g for 15-20 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%